2014
DOI: 10.3390/rs61212544
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological Impacts of Urbanization of Two Catchments in Harare, Zimbabwe

Abstract: By increased rural-urban migration in many African countries, the assessment of changes in catchment hydrologic responses due to urbanization is critical for water resource planning and management. This paper assesses hydrological impacts of urbanization on two medium-sized Zimbabwean catchments (Mukuvisi and Marimba) for which changes in land cover by urbanization were determined through Landsat Thematic Mapper (TM) images for the years 1986, 1994 and 2008. Impact assessments were done through hydrological mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 69 publications
2
13
0
2
Order By: Relevance
“…As impervious area increases, less water infiltrates into the soil resulting in lower soil water storage. Several studies have investigated the correlation between urbanization and the water balance in tropical regions (Wagner et al, 2013;Gumindoga et al, 2014a;Remondi et al, 2016) and results are similar to ours.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…As impervious area increases, less water infiltrates into the soil resulting in lower soil water storage. Several studies have investigated the correlation between urbanization and the water balance in tropical regions (Wagner et al, 2013;Gumindoga et al, 2014a;Remondi et al, 2016) and results are similar to ours.…”
Section: Discussionsupporting
confidence: 70%
“…Numerous studies argue that different types of land use have different water use and water storage characteristics, thus different land use distributions may result in different distributions of water in space and time (Bruijnzeel, 1989;Sahin & Hall, 1996;Brown et al, 2005;Romanowicz & Booij, 2011;Gumindoga et al, 2014a;Zhang et al, 2016;Marhaento et al, 2017a). Studies in tropical regions have shown that changes from vegetated areas into settlements may significantly reduce canopy interception and soil infiltration capacity, resulting in a large fraction of precipitation being transformed into surface runoff (Bruijnzeel, 2004;Valentin et al, 2008;Marhaento et al, 2017a).…”
Section: Introductionmentioning
confidence: 99%
“…Alternative methods have been developed in recent years which provide rapidly available hydrological data over large areas based on remote-sensing techniques. Satellite data can be used to: derive terrain parameters using freely available elevation data (Maathuis and Wang, 2006;Gumindoga et al, 2011), estimate soil moisture (Horváth, 2002;Meier et al, 2011), estimate rainfall (Habib et al, 2012;Haile et al, 2013), quantify evapotranspiration Rientjes et al, 2013) and determine landcover parameters (Dube et al, 2014;Gumindoga et al, 2014a;Gumindoga et al, 2014b).…”
Section: Introductionmentioning
confidence: 99%
“…Parameters were calibrated for a reference period and the simulated runoff compared to observed runoff in periods with potential change (Seibert and McDonnell, 2010). To detect if there has been any changes as a result of land use, all the optimized parameters and the input variables derived from running the model for the period 2000 to 2008 were held constant as in Gumindoga et al (2014), then the land cover parameters were varied to 1989, 1998 and 2014 ones and the model simulated again to observe if there were any differences to the runoff simulated In the model setup, only the catchment characteristics derived from land cover maps were changed, the precipitation, temperature and evapotranspiration values which were applied to simulations for the period 1998 to 2008 remained unchanged thus model forcing re- The "+" sign means an increasing trend and the "−" sign means a decreasing trend. *: statistically significant at 5 % level.…”
Section: Model Application For Land Cover Change Impactsmentioning
confidence: 99%
“…The recent interests towards integrated management of land and water has renewed the need of quantifying the hydrological impacts of land use changes (Gumindoga et al, 2014) The integrated management of land and water resources will facilitate more productive and sustainable utilisation of the natural resources available in the basin.…”
Section: Introductionmentioning
confidence: 99%